Development of interactive e-books on creative dance to enhance middle school students' appreciation of art - Nanda Rochmahningtyas; Anik Juwariyah; Retnayu Prasetyanti Sekti; Arif Hidajad; Norsafini Jafar (Jurnal Inovasi dan Teknologi Pembelajaran, 2025)
The development of the digital globalisation era demands that teachers adapt to technology, including in the creation of dance teaching materials that require visualisation and interactive experiences. Conventional media such as printed books are less effective because they lack visual or audio elements, limiting students' understanding of movements, floor patterns, and the meaning of dance. Previous studies only focused on text or single videos, so interactive e-books for creative dance materials are needed because they can provide contextual, attractive learning that aligns with the characteristics of the digital generation. This study aims to develop a multimedia-based interactive dance e-book (including video, audio, animation, and interactive quizzes) using the 4D model. The research method used validation sheets, quantitative descriptive analysis, and limited trials on 30 students of class IX at SMP Negeri 10 Madiun. The validation results showed an average score of 3.42, categorised as very valid. Meanwhile, student responses showed high appreciation for observation aspects at 92%, internalization at 90%, and meaning-making and critical assessment at 87%. It is concluded that the interactive e-book is effective in facilitating dance comprehension, increasing motivation, art appreciation, and learning engagement. Its effectiveness in enhancing art appreciation averaged 11.8% with a normalised n-gain score of 0.46, categorised as medium. Substantively, this study is able to improve cognitive understanding, strengthen students' art appreciation, affective, and psychomotor skills, thus serving as an adaptive cultural art learning medium in the digital era.